Empowering MSMEs through digital marketing assistance at Baitul Mal Banda Aceh - Inayatillah Djakfar; Isnaliana; Nor Azzah Kamri; Nining Puji Rahayu; Sirriyatul Maula (University of Merdeka Malang, 2025)
In the current era of rapid technological advancement, digital marketing has become a vital strategy for business sustainability and growth, especially among Micro, Small, and Medium Enterprises (MSMEs). Effective and efficient use of digital marketing tools can significantly enhance market reach, increase brand awareness, and ultimately improve sales performance while reducing operational costs. Nevertheless, many MSMEs still face barriers in adopting digital platforms due to limited knowledge and technical skills. This community outreach initiative provides structured and targeted digital marketing assistance to MSMEs affiliated with Baitul Mal Banda Aceh. The mentoring model consists of five key stages: (1) needs identification and analysis, (2) mentoring plan development, (3) implementation of mentoring sessions, (4) monitoring and evaluation, and (5) reporting of outcomes. The results indicate a noticeable improvement in participants’ understanding of digital marketing concepts and platforms. Most MSMEs successfully created and managed social media accounts (Instagram and TikTok) and utilized e-commerce and food delivery platforms such as GrabFood and GoFood for product promotion. Participants also demonstrated increased confidence and independence in designing promotional content using digital tools. Overall, the program received positive responses from participants and shows strong potential for sustainability as a community-based digital empowerment model for MSMEs.